Реалії та перспективи розвитку кадрового потенціалу підприємств будівельної галузі - Kalinіchenko, Liudmila; Smachylo, Valentyna; Khalina, Veronika (Dr. Viktor Koval, 2019)
Introduction. The relevance of studying realities and perspectives of human resources development is predetermined by the growing importance of the role and place of man in all socioeconomic processes. At the same time, these studies become significant within certain branches, including the construction industry, which is the main driver of the economic development of the region and the country as a whole. Aim and tasks. Determining realities and perspectives of human resources development of construction companies, which includes: research of the dynamics of indicators on labor in the field of construction; definition of prediction trends of the basic labour indicators in the construction sector and their predictive values; development of a model which determines the power of influence and interrelation between the level of remuneration and the volume of construction works, as well as enables to determine the number of employees in the construction sector, depending on the values of the selected factors; determining specific features of human resources development in the construction sphere. Results. The use of dynamics series enables to determine the realities and reveal trends in the sphere of the construction industry, among which we have established the reduced number of employees, increased wages in the construction sphere, the high intensity of migration, increased volumes of construction works, almost the same number of vacancies in absolute terms; by means of economic forecasting methods, we have established optimal predictive equations: the third-order polynomial function for the indicator of the number of employees in the construction industry; the second-order polynomial function for the volume of the construction works performed; the second-order polynomial function for the average monthly remuneration, and we have calculated the predictive values of the main indicators in the work area; regression and correlation analysis enables to reveal the level of interconnection between the number of employees in the construction sphere, the volume of construction works and remuneration, which will determine the number of employees in the construction industry depending on the factors of influence: insignificant, but direct impact on the level of remuneration, and more powerful, but adverse effect of the volume of construction works. This is the basis for making managerial decisions on the development of human resources in the construction industry. The authors have summarized the peculiarities of the construction industry with regard to the development of human resources in three main directions, namely: peculiarities of personnel training for the sphere of construction, peculiarities of employment and peculiarities of personnel management in the construction industry. Conclusions. We have established the necessity of further development and improvement of the process of human resources development in the construction industry, from the change of approaches to personnel training and the search for up-to-date and effective methods of personnel management, which, in turn, will lead to positive changes in the construction sphere and, accordingly, will give impetus to the development of the economy as a whole..